2003
DOI: 10.1016/s0043-1648(03)00246-1
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale study of friction and energy dissipation

Abstract: This paper presents an analysis of the interaction energy and various forces between two surfaces, and the microscopic study of friction. Atomic-scale simulations of dry sliding friction and boundary lubrication are based on the classical molecular dynamics (CMD) calculations using realistic empirical potentials. The dry sliding of a single metal asperity on an incommensurate substrate surface exhibits a quasi-periodic variation of the lateral force with two different stick-slip stage involving two structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We are taught that sliding friction involves the conversion of mechanical energy into heat [1,2] and that this conversion necessarily is irreversible [3]. The microscopic picture that is usually associated with this conversion involves phonons [4][5][6] that are excited within the sliding bodies, typically through mechanical instabilities, such as stick-slip events. Due to phonon coupling and the associated, finite phonon lifetimes [7][8][9][10], the energy that specific phonon modes acquire from these instabilities is thought to be quickly redistributed over the full spectrum of possible phonons.…”
Section: Introductionmentioning
confidence: 99%
“…We are taught that sliding friction involves the conversion of mechanical energy into heat [1,2] and that this conversion necessarily is irreversible [3]. The microscopic picture that is usually associated with this conversion involves phonons [4][5][6] that are excited within the sliding bodies, typically through mechanical instabilities, such as stick-slip events. Due to phonon coupling and the associated, finite phonon lifetimes [7][8][9][10], the energy that specific phonon modes acquire from these instabilities is thought to be quickly redistributed over the full spectrum of possible phonons.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic-scale simulations of Ni-Ni interface dry sliding friction and boundary lubrication were carried out by Ciraci et al [70] using classical molecular dynamics (CMD) calculations adopting empirical potentials. Results indicated that sliding of a single metal asperity on an incommensurate substrate surface exhibits a quasi-periodic variation of the lateral force with two different stick-slip stage involving two structural transformation followed by a wear.…”
Section: Atomic-scale Metal Interfacesmentioning
confidence: 99%
“…Our approach 19 allows us to calculate the friction coefficient by knowing the tip–surface interaction potential. The potential can be theoretically obtained by using ab initio calculations 20, 21, experimentally or using dynamic force microscopy (DFS) 22–25.…”
Section: Introductionmentioning
confidence: 99%